Eco-Cultural Niche Breadth and Overlap Within the Cucuteni–Trypillia Culture Groups During the Eneolithic - Mihu-Pintilie, Alin; Gherghel, Iulian (Frontiers in Earth Science, 2022)
One of the most applied tools for documenting cultural variability and tracing the cultural trajectories within the environmental context is Eco-Cultural Niche Modeling and its associated methodology. The niche breadth characterization quantitatively evaluates the links between a given adaptive system and ecological constraints, which provides valuable information for archaeology. For this purpose, in this study, ten independent climatic and topographic environmental variables were interpolated, and eco-cultural niche modeling techniques were used to determine whether these differences in the geographic distributions and niche breadth are consequences of differences for five Cucuteni–Trypillia groups that flourished in Eastern Europe during the Eneolithic (cal. 5,400/5,300 – 2,800/2,700 BCE). Our results show that the eco-cultural niche of Cucuteni–Trypillia groups are significantly overlapping, and the expansion trend of the last two cultural groups (Late Eneolithic – cal. 4,100/4,000 – 2,800/2,700 BCE) into the northeastern steppe regions was not due to ecological niche differences but rather a result of other cultural factors. Furthermore, we highlighted that the first three Cucuteni–Trypillia groups (Early to Middle Eneolithic – cal. 5,400/5,300 – 4,100/4,000 BCE) had slightly more constrained ecological niches in the mid-Holocene ecosystems than Late Eneolithic groups. The results have significant implications for understanding the geographical range dynamics and distribution of the last great Chalcolithic society of Old Europe and contribute to the characterization of ecological niches they have exploited during the cultural evolutionary process.